2012
DOI: 10.1155/2012/584725
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Facial, Prosodic, and Social Context Emotional Recognition in Early-Onset Schizophrenia

Abstract: The purpose of the present study was to determine sex differences in facial, prosodic, and social context emotional recognition in schizophrenia (SCH). Thirty-eight patients (SCH, 20 females) and 38 healthy controls (CON, 20 females) participated in the study. Clinical scales (BPRS and PANSS) and an Affective States Scale were applied, as well as tasks to evaluate facial, prosodic, and within a social context emotional recognition. SCH showed lower accuracy and longer response times than CON, but no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
(65 reference statements)
2
9
0
Order By: Relevance
“…Emotional processing assessed by the Penn Emotion Recognition Test was also found to be enhanced in SP and HC females compared with males (Calkins et al, 2013). Another study reported sex differences in social context emotions where females of SP and HC groups showed greater empathy than males with respect to happiness (Ramos-Loyo et al, 2012). Finally, sex differences in olfactory processing have been observed, with better smell identification found in SP and HC females assessed by the University of Pennsylvania Smell Identification Test (Malaspina et al, 2012a;Malaspina et al, 2012b).…”
Section: Sex Differences Shared Between Patients With Schizophrenia Amentioning
confidence: 88%
See 1 more Smart Citation
“…Emotional processing assessed by the Penn Emotion Recognition Test was also found to be enhanced in SP and HC females compared with males (Calkins et al, 2013). Another study reported sex differences in social context emotions where females of SP and HC groups showed greater empathy than males with respect to happiness (Ramos-Loyo et al, 2012). Finally, sex differences in olfactory processing have been observed, with better smell identification found in SP and HC females assessed by the University of Pennsylvania Smell Identification Test (Malaspina et al, 2012a;Malaspina et al, 2012b).…”
Section: Sex Differences Shared Between Patients With Schizophrenia Amentioning
confidence: 88%
“…When comparing male and female SP groups for symptom profiles, most of the studies reported more severe negative symptoms in males (Moriarity et al, 2001;Ramos-Loyo et al, 2012;Torniainen et al, 2011;Zhang et al, 2012a) while more severe positive symptoms in males have been observed by others (Roesch-Ely et al, 2009).…”
Section: Sex Differences Specific To Patients With Schizophreniamentioning
confidence: 89%
“…MET = Multifaceted Empathy Test. **The emotion intensity task used in the study by Ramos-Loyo & colleagues (Ramos-Loyo et al, 2012) had individuals provide a self-reported rating of the emotion they experienced while watching an emotion-evoking film, along with the intensity of that emotion. *These effect sizes were not included in the meta-analysis because other effects produced by the same sample were used instead, based on guidelines laid out in the Methods.…”
Section: Discussionmentioning
confidence: 99%
“…These attributes should render sad sounds as signals of reduced salience. Previous studies have reported significant deficits in the prosodic perception of sad stimuli in SPs [59,62], which could compromise accuracy in the identification of sad sounds [63]. Our findings of delayed brain responses to sad sound in all schizophrenia groups (for past and/or concurrent AH) suggest that a reduction in the ability to perceptually process less emotionally salient environmental stimuli may be a characteristic trait of schizophrenia.…”
Section: Discussionmentioning
confidence: 42%